Feasibility and acceptability of telehealth coaching to promote healthy eating in chronic kidney disease: a mixed-methods process evaluation. Issue 1 (29th January 2019) - Kelly, Jaimon T; Warner, Molly M; Conley, Marguerite; Reidlinger, Dianne P; Hoffmann, Tammy; Craig, Jonathan; Tong, Allison; Reeves, Marina; Johnson, David W; Palmer, Suetonia; Campbell, Katrina L
Abstract : Objective: To evaluate the feasibility and acceptability of a personalised telehealth intervention to support dietary self-management in adults with stage 3–4 chronic kidney disease (CKD). Design: Mixed-methods process evaluation embedded in a randomised controlled trial. Participants: People with stage 3–4 CKD (estimated glomerular filtration rate [eGFR]15–60 mL/min/1.73 m 2 ). Setting: Participants were recruited from three hospitals in Australia and completed the intervention in ambulatory community settings. Intervention: The intervention group received one telephone call per fortnight and 2–8 tailored text messages for 3 months, and then 4–12 tailored text messages for 3 months without telephone calls. The control group received usual care for 3 months then non-tailored education-only text messages for 3 months. Main outcome measures: Feasibility (recruitment, non-participation and retention rates, intervention fidelity and participant adherence) and acceptability (questionnaire and semistructured interviews). Statistical analyses performed: Descriptive statistics and qualitative content analysis. Results: Overall, 80/230 (35%) eligible patients who were approached consented to participate (mean±SD age 61.5±12.6 years). Retention was 93% and 98% in the intervention and control groups, respectively, and 96% of all planned intervention calls were completed. All participants in the intervention arm identified the tailored text messages as useful in supporting dietary self-management. In the control group, 27 (69%) reported the non-tailored text messages were useful in supporting change. Intervention group participants reported that the telehealth programme delivery methods were practical and able to be integrated into their lifestyle. Participants viewed the intervention as an acceptable, personalised alternative to face-face clinic consultations, and were satisfied with the frequency of contact. Conclusions: This telehealth-delivered dietary coaching programme is an acceptable intervention which appears feasible for supporting dietary self-management in stage 3–4 CKD. A larger-scale randomised controlled trial is needed to evaluate the efficacy of the coaching programme on clinical and patient-reported outcomes. Trial registration number: ACTRN12616001212448; Results.